Associations of osteoclastogenesis and nerve growth in subchondral bone marrow lesions with clinical symptoms in knee osteoarthritis - Feng Zhou; Xuequan Han; Liao Wang; Weituo Zhang; Junqi Cui; Zihao He; Kai Xie; Xu Jiang; Jingke Du; Songtao Ai; Qi Sun; Haishan Wu; et al. (Journal of Orthopaedic Translation, 2022)
Background/objective: Subchondral bone marrow lesions (BMLs) are common magnetic resonance imaging (MRI) features in joints affected by osteoarthritis (OA), however, their clinical impacts and mechanisms remain controversial. Thus, we aimed to investigate subchondral BMLs in knee OA patients who underwent total knee arthroplasty (TKA), then evaluate the associations of osteoclastogenesis and nerve growth in subchondral BMLs with clinical symptoms. Methods: Total 70 patients with primary symptomatic knee OA were involved, then separated into three groups based on MRI (without BMLs group, n ​= ​14; BMLs without cyst group, n ​= ​37; BMLs with cyst group, n ​= ​19). Volume of BMLs and cyst-like lesions was calculated via the OsiriX system. The Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) questionnaire was used to assess clinical symptoms. Histology and immunohistochemistry were deployed to assess subchondral osteoclastogenesis and nerve distribution. Pearson's correlation coefficient was used to evaluate the associations between volume of BMLs and joint symptoms, and to assess the associations of osteoclastogenesis and nerve growth in subchondral BMLs with joint symptoms. Results: In BMLs combined with cyst group, patients exhibited increased osteoclastogenesis and nerve distribution in subchondral bone, as shown by increased expression of tartrate resistant acid phosphatase (TRAP) and protein gene product 9.5 (PGP9.5). Volume of subchondral cyst-like component was associated with joint pain (p ​< ​0.05). Subchondral osteoclastogenesis and nerve distribution were positively associated with joint pain in BMLs with cyst group (p ​< ​0.05). Conclusion: The subchondral cyst-like lesion was an independent factor for inducing pain in OA patients; osteoclastogenesis and nerve growth in subchondral cyst-like lesions could account for this joint pain. The translational potential of this article: Our results indicated that the increased osteoclastogenesis and nerve growth in subchondral cyst-like lesions could account for the pain of OA joints. These findings may provide valuable basis for the treatment of OA.